Understanding the Role of Response Surface Methodology in Development of Quercetin Loaded Phytocomplex for Wound Healing - Rajendra, Jangde (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: It has been proved that optimized quercetin-loaded phytocomplex (QLP) system using response surface methodology occupied the desired characteristic for wound healing. Materials and Methods: The phytocomplex was prepared using complexation method. Quercetin and phosphatidylcholine were mixed by adding 20 mL of dichloromethane. The whole solution was refluxed for 2 h by maintaining the temperature below 60Â°C. The resulting solution was evaporated to 2-3 mL, and 10 mL of n-hexane was mixed with continuous stirring to form complex. Results and Discussion: According to entrapment efficiency (EE), drug release (DR), and percentage yield (PY) of phytocomplex concentration of quercetin (100 mg) and phospholipids (100 mg) were in optimum quantity. Physical characteristic were evaluated through in vitro characterization of phytocomplex including the EE, DR, and PY the resulting values of 82.10%, 61.96%, and 76.36% were found to be standard characterized values respectively. Conclusion: Optimized QLP will provide us an innovative platform as a novel addition to achieve high therapeutic efficacy on wound space.